Potential of liquid smoke and rosemary (Salvia rosmarinus) extract as antimicrobial and antioxidant in corn starch-based edible coating - Satar, Ibdal; Azizah, Siti Nur (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Edible coatings are thin films that cover the surface of products to prevent the physical, chemical and/or biological damages. So far, the edible coatings still have shortcomings, especially in terms of antioxidant and antimicrobial properties. The use of corn starch (CS) combined with the addition of liquid smoke (LS) and rosemary extract (RE) is believed to improve the quality of edible coatings. This work aims to evaluate the performance of edible coatings made from CS with the addition of LS and RE. Formulations were tested with LS and RE ratios F0 (0:0), F1 (6:0), F2 (4:2), F3 (3:3), F4 (2:4), and F5 (0:6). The quality of edible coatings was evaluated based on the antioxidant and antimicrobial activities. Both antioxidant and antimicrobial activities were analysed using the 2-2-diphenyl-1-picrylhydrazyl (DPPH) and total plate count (TPC) methods. The data were statistically analysed using one-way ANOVA with a significance level of 0.05. Antioxidant activities (IC50) of edible coatings were obtained in the range of 59.49-194.55 ppm. Meanwhile, the antimicrobial activities were observed less than 1 x 105 cfu/g (not detected). Compared to the F0 formulation (control) without LS and RE, the F4 formulation exhibited the most favorable properties, as evidenced by its lowest IC50 value and highest total phenolic content (TPC). In conclusion, the incorporation of LS and RE effectively enhanced the antioxidant and antimicrobial activities of the edible coatings.